The use of a simple and affordable skin patch for measurement of transcutaneous bilirubin levels in neonates during phototherapy - Kallimath, Aditya; Patnaik, Suprabha; Suryawanshi, Pradeep; Deshmukh, Rupeshkumar; Malshe, Nandini (Frontiers in Pediatrics, 2024)
Background Transcutaneous bilirubin (TcB) measurements during and after phototherapy for hyperbilirubinemia must be performed on unexposed skin. There are commercially made skin patches for this purpose, but they are relatively unavailable in low-resource settings. We devised a simple cotton patch and tested its use for TcB during phototherapy. Methods Measurements were taken in healthy neonates born at a gestational age of ≥35 weeks who were undergoing phototherapy for hyperbilirubinemia in western India before, 12 h after the start, and 12 h after the end of phototherapy. Total serum bilirubin (TSB) was measured using the diazo method in a clinical laboratory. TcB measurements were performed using a Dräger Jaundice Meter JM-105 placed over the sternum on two skin areas that were protected during and after treatment by a commercial (Philips BilEclipse) or self-made patch comprised of cotton gauze and wool. Results In total, 47 neonates were included in our study. Before phototherapy, TSB and TcB values had a strong correlation (Pearson, r = 0.88), with a mean difference of −1.35 mg/dl. Correlations with TSB were good and equivalent for TcB values measured on skin covered by the commercial and self-made patches during (0.78 and 0.70, respectively) and after (0.57 and 0.58, respectively) phototherapy. TcB values measured on skin covered by the two patches correlated well both during and after phototherapy, with r = 0.82 and 0.90, respectively, and mean (95% confidence interval) differences of −1.21 and −0.32 mg/dl, respectively. Conclusions Reliable TcB measurements taken during and after phototherapy can be achieved on skin covered with a simple and affordable cotton skin patch.